Risk factors and outcome of asparaginase-associated pancreatitis in pediatric acute lymphoblastic leukemia - Hassan, Seham; Ahmed, Sonia; Ali, Nesreen; Mokhles, Abeer; Zaky, Iman; Reda, Hala; Youssef, Sarah H.; Hammad, Dina; Hassanain, Omneya; Sidhom, Iman (Frontiers in Oncology, 2025)
BackgroundAsparaginase-associated pancreatitis (AAP) poses a significant challenge in pediatric patients with acute lymphoblastic leukemia (ALL), with its severity ranging from mild cases to potentially life-threatening conditions.AimTo study the incidence, risk factors of AAP, and its impact on outcome in pediatric ALL patients in a large pediatric oncology hospital in a low-and middle-income country.Patient and methodsThis retrospective study included 1804 pediatric patients newly diagnosed with ALL at a single tertiary care center from June 2012 to December 2017. They were treated with ALL protocol adopted from St Jude total study XV including native E. coli L-asparaginase.ResultsSixty-three (3.5%) patients experienced AAP. Age ≥10 years at diagnosis, initial white blood cell count (WBC) ≥50x109/L, and standard/high-risk treatment regimen were significantly associated with developing AAP. By multivariate analysis, age ≥10 years and high-dose asparaginase regimens remained significant risk factors for AAP. Mild/moderate AAP was reported in 47 (75%) patients without associated mortality, however, 6/16 (37.5%) patients with severe pancreatitis died. Asparaginase was re-challenged in 39/63 (62%) patients of whom 12 patients (30.8%) experienced recurrent AAP without mortality. Patients who were not re-exposed to asparaginase had a relapse rate of 37.5% compared to 23% for those who were re-challenged. The 5-year event-free-survival (EFS) and cumulative incidence of relapse (CIR) were 63.5% and 24.3%; respectively; for patients with AAP compared to 77% and 14.4% for those without AAP (P=0.01, P=0.02; respectively). However, AAP lost its significant impact when adjusted to other factors including age, WBC, immunophenotype, and ALL risk stratification (EFS: HR1.32; 95%CI, 0.88-1.98; P=0.17 and CIR: HR1.44; 95%CI, 0.86-2.4; P=0.16).ConclusionOlder age and high-dose asparaginase regimens are independent risk factors of AAP. The decision to re-challenge asparaginase should be carefully considered balancing the risk of recurrent pancreatitis against the potential risk of leukemic relapse.